Attitudes towards the dying and death anxiety in acute care nurses – can a workshop make any difference? A mixed-methods evaluation. Issue 2 (April 2020) - Cheong, Chin Yee; Ha, Ngoc Huong Lien; Tan, Laurence Lean Chin; Low, James A.
Abstract: Objectives: In Singapore, the core curriculum for end-of-life (EOL) care used in nurse training courses is limited. Only 45% of nurses indicated familiarity with inpatient palliative care. Nurses who lack skills in palliative care may develop anxiety and negative attitudes towards caring for dying patients. We explored whether a two-day, multimodal EOL care workshop could reduce nurses' death anxiety and improve nurses' skills, knowledge, and attitude towards palliative care. Methods: Forty-five nurses participated in the workshop. At baseline before and at six weeks after, a 20-item knowledge-based questionnaire and the Death Attitude Profile-Revised (DAP-R) were administered. Six weeks post-workshop, in-depth interviews were conducted. We employed descriptive statistics, student paired samples t -test and inductive thematic analysis. Results: There was a significant improvement in nurses' knowledge score ( p < 0.01) and reduction in their death anxiety score ( p < 0.01). Fear of Death ( p = 0.025) and Death Avoidance ( p = 0.047) sub-scores decreased significantly. However, the remaining domains such as Neutral Acceptance, Approach Acceptance, and Escape Acceptance did not show any significant difference, although Escape Acceptance showed a trend towards a reduced score ( p = 0.063). After the workshop, more nurses adopted the Neutral Acceptance stance (76.2%), and none of them fell into the Fear of Death subdomain. Most nurses interviewed reported a positive change in their knowledge, attitudes, and practice even after the workshop. Significance of results: The multimodal palliative care workshop was useful in improving nurses' EOL knowledge and reducing their anxiety towards death. The positive change in nurses' attitudes and practices were noted to be sustained for at least six weeks after the intervention.